Experience in providing care to women victims of violence in Consultorios Rosa, Cali, Colombia - Estrada Duque , Yivi Yohana; Otálvaro Marin, Liliana (Interdisciplinary Journal of Epidemiology and Public Health, 2024)
Objective: To describe the care process received by women victims of gender violence in intimate partner relationships through the strategy of the Consultorios Rosa (hillside health networkESE and north health network ESE) in Cali during the period 2020 – 2022. Methods: Was carried out qualitative research of a phenomenological type from the study on women victims of intimate partner violence. Through the development of semi-structured interviews, the experiences of health care in the pink office strategy, which operates in the primary care centers in Cali, Colombia, were analyzed. Results: The violence against women in couple relationships was caused by multiple violent expressions that affect emotional, mental, and physical health and exposure to femicide. The Consultorios Rosa strategy represents an opportunity for women to make the initial recovery and can address the situation experienced and give it new meaning; however, the strategy is susceptible to improvements that restore women’s rights in the health sector. Conclusions: Women continue to be victims of psychological, emotional, physical, economic, and sexual abuse, experiencing violent situations in their relationships; all violent expressions affect their health, well-being, and life, evidencing emotional, mental, and physical consequences. Therefore, it continues to be a priority public health problem to intervene. Public health strategies play a crucial role in the recovery of women victims of violence. However, their scope is underestimated if the interventions are not accompanied by timely access to justice. Interdisciplinary and interinstitutional care is necessary to provide comprehensive services to women victims of violence from the health sector.